2021
DOI: 10.1002/brb3.2142
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for early–onset seizures after stroke: A systematicreview and meta‐analysis of 18 observational studies

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(119 reference statements)
2
9
0
Order By: Relevance
“…This study found that there was no statistically significant difference between the three groups as regard history of diabetes mellitus, hypertension, heart diseases, atrial fibrillation, carotid stenosis and collagen diseases. In agreement with a study found that the above factors have no obvious relationship with the occurrence of early seizures [8]. In contrast to a study showed that there is a high correlation between hypertension, diabetes mellitus, heart diseases and the occurrence of early seizures [9].…”
Section: Discussionsupporting
confidence: 89%
“…This study found that there was no statistically significant difference between the three groups as regard history of diabetes mellitus, hypertension, heart diseases, atrial fibrillation, carotid stenosis and collagen diseases. In agreement with a study found that the above factors have no obvious relationship with the occurrence of early seizures [8]. In contrast to a study showed that there is a high correlation between hypertension, diabetes mellitus, heart diseases and the occurrence of early seizures [9].…”
Section: Discussionsupporting
confidence: 89%
“…Our study indicated that HT and sICH are risk factors for earlyonset seizures. A meta-analysis showed that the incidence of earlyonset seizures in the intracerebral haemorrhage group was greater than that in the cerebral infarction group [41], which provides support for our conclusion. The pathogenesis might be explained by the epileptogenic effect of blood degradation products on cortical neurons.…”
Section: Discussionsupporting
confidence: 81%
“…It was found that patients with severe strokes, cortical involvement and large‐vessel occlusion are more likely to receive EVT. However, several studies have reported that the independent risk factors for PSS include the severity of stroke, large‐artery atherosclerotic aetiology, cortical involvement and middle cerebral artery involvement [5, 10, 40–42]; these factors were combined into a predictive model named SeLECT to predict the occurrence of PSE [6]. Therefore, patients who received EVT are more likely to be associated with subsequent seizures compared to those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Post-stroke seizures are associated with a worse functional outcome, a higher mortality rate and increased risk of comorbidities [4]. Many risk factors of PSSs (cortical involvement, haemorrhagic transformation, intracerebral haemorrhage [5] and baseline stroke severity [6]) have been identified; however, the role of endovascular treatment (EVT) for PSSs is controversial. Several articles have reported that the underlying mechanisms leading to PSS include reperfusion syndrome [7], subsequent inflammatory reaction [8] and haemorrhagic complication [9], whilst other studies did not confirm these findings [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%